Binoh Pottery MSME marketing expansion through digital marketing strategy - I Made Riski Aditya Darma; Kadek Devi Kalfika Anggaria Wardani; Adie Wahyudi Oktavia Gama (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Intense competition and the digital ecosystem have hampered the growth of Binoh's typical pottery MSMEs. Based on problems, the Binoh Pottery MSMEs in Ubung Kaja Village can reach the digital world and a broader market through training and the application of digital-based business. Thus, MSME entrepreneurs can market and promote products through digital channels. Through a series of planned activities, this community service activity aims to provide education on the application of digital business to the Pottery MSMEs in Binoh Village. By using the Participatory Rural Appraisal (PRA) method, the activities are divided into four major stages, namely initial initiation and planning, implementation, supervision, and evaluation. Based on the results of observations and evaluations, it is known that the response of MSMEs actors is very positive to the education provided. MSMEs actors view digital marketing as having an important role to help their businesses survive. It is hoped that in the next stage the government will take an active role in developing Binoh typical pottery MSMEs, Ubung Kaja Village. Not only as a form of effort to move the people's economic sector but also as an effort to maintain pottery as traditional Balinese art.